Bugis in Sabah and GE-14: Case Study of Kalabakan Parliament - Amrullah Maraining; Zaini Othman; Eko Prayitno Joko; Saat Awang Damit (2018)
In the context of Malaysia, the politics of ethnic diversity often focus on Malays, Chinese and Indians. This is probably influenced by the historical background of the country concerned with the declaration of independence on August 31, 1957 which was obtained by the agreement of these three ethnic groups under the Alliance Party umbrella. This ethnic collective agreement continued until Sabah and Sarawak together with the Federation of Malaya formed Malaysia on 16 September 1963. The historical fact of witnessing the sharing of some of the major events of the country is that sometimes from the other side of the minds of academic or non-academic groups sometimes become narrow and tangled its nature. As a result, the dimensions of national political studies, especially on ethnic politics are often bombarded by writing focusing on Malay, Chinese and Indian as subjects especially in the run-up to the general elections. It is rarely highlighted by other ethnicities, especially in Sabah and Sarawak which also play a very significant role in determining the country’s political direction. One of them is the Bugis community on the east coast of Sabah, which is based on Sabah’s historical background that its involvement in Sabah’s political arena, especially for the Kalabakan parliament by the GE-14 which is rarely studied. Recognizing the caps, this paper is to highlight the role and existence of Bugis communities in Sabah especially in the context of Sabah politics, especially the east coast. In understanding this reality the method used to obtain information and data is through direct interviews of respondents involved in the political leadership of the government or opposition.